Goal-Setting Appraisal and Employee Motivation of Education in Public sector Organization: A Literature Studies - Yul Windiya Rini; Dwi Arini Mandasari; Iriani Ismail (Edumaspul: Jurnal Pendidikan, 2023)
Employee performance appraisal is an important process in organizational performance management, including in the public sector. Goal-setting appraisal is an increasingly popular performance appraisal method in the public sector. The purpose of this research is to describe the goal-setting appraisal strategy in increasing employee motivation in public sector organizations. This research was conducted through a literature study that collected and analyzed the results of previous research on the impact of goal-setting appraisal on employee motivation, the factors that influence it, along with strategies for determining goal-setting appraisal. The results of this study indicate that goal-setting appraisal has a positive and negative impact on employee motivation. Factors that influence goal-setting appraisals on work motivation include goal certainty, organizational commitment, social support, self-efficacy, and job satisfaction. In addition, there are several strategies that can be implemented by organizations in determining effective goal-setting appraisals. increasing employee motivation and organizational performance. This research can provide recommendations for practitioners and managers in the public sector to develop more effective performance management policies and practices.